Analisis Resiko Keuangan Pada PT. Bank Central Asia Tbk. Dengan Menggunakan Metode Altman Z-Score - Cahyono, Ikhsan; , Drs. Ma'ruf, M.M (2015)
This research aimed to analyze the financial risk to the PT. X indicated bankrupt or not, using the Altman Z-Score. Based on the results of the data analysis of the financial statements. X. In 2012 obtained Z-Score of 1.338. In 2013 obtained the value Z-Score of 1,425. 2014 obtained the value Z-Score of 1.545. Based on the criteria Altman Z-Score, values <1.81 are categorized as the company predicted bankruptcy because it has a very large financial risk. So it can be concluded that PT. X. years of 2012-2014 predicted will be bankrupt within three years if not immediately to repair the company's performance, because it has a financial risk large enough. Keywords: Balance Sheet, Profit and Loss, Z-Score, bankrupt.